Simple and best practice solution for 3x^9+6x^8-9x^7+6x^6= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.
If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Solution for 3x^9+6x^8-9x^7+6x^6= equation:
Simplifying 3x9 + 6x8 + -9x7 + 6x6 = 0 Reorder the terms: 6x6 + -9x7 + 6x8 + 3x9 = 0 Solving 6x6 + -9x7 + 6x8 + 3x9 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3x6'. 3x6(2 + -3x + 2x2 + x3) = 0 Ignore the factor 3.
Subproblem 1Set the factor 'x6' equal to zero and attempt to solve: Simplifying x6 = 0 Solving x6 = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x6 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(2 + -3x + 2x2 + x3)' equal to zero and attempt to solve: Simplifying 2 + -3x + 2x2 + x3 = 0 Solving 2 + -3x + 2x2 + x3 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
See similar equations:
| .66(9b-27)=36 | | .75-.33z=.25 | | 3y-2=28-3y | | 9x+5y=1 | | u^2+8u+7=0 | | 3x^2+14x+18=0 | | x-17=5-3 | | 3y+9x=12 | | 2b+9=3 | | 14=7y-6x | | 4b-6=-18 | | 124=4x-10y | | 12-11a=45 | | 6+4x=3(6x+9) | | 6.4x=.33(6x+9) | | 1-7x=2-y | | 5+r=-19 | | 400+50w=1200 | | -11x=-77 | | n-12=73 | | -20=-9-(-m) | | (-m)-(-9)=-20 | | y+(-3)=12 | | 2n=(-70) | | -5n=40 | | -20=(-4) | | -20=(-4n) | | 96C= | | .05y=30 | | 4c-8c+7=37 | | F=20-4 | | 8x-8y=3 | | -19.4-15d+22d=4.4 | | 6x^2+6x-12=0 | | -12h+39=54+6n | | -5.7v-44.2=-8.3v | | 9x-3y=1 | | m-2n=16 | | 2n+3=11 | | -3n-4=(-19) | | 4=10t-6 | | 2(x-3)=2 | | 15=22x+7 | | 15x^2-14x=0 | | 14=2(3x-2) | | 5n+4=7(m+1)-2n | | 5n+4=7(n+1)-2n | | 12X^6+8X^4=6 | | 12X^6+8X^4=0 | | 12X^6+8X^6=0 | | -2(a+k)(a-k)=0 | | -2(a+k)(a-k)= | | 8=3x+11 | | 6x+5=8(r+2)-2x | | x^2-9x^2=40 | | 3(z-2)+6=5(z+4) | | 3t-11=5-t | | 3(x-11)=12 | | 4-3x=7x-6 | | bx-10=-2 | | 8+4x=-10+x | | b(-2)-10=-2 | | 12(x*x)+x-12=0 | | x-0.1x+0.07(x-0.1x)=69.62 | | 7x-3=10x+15 |